Effects of oxygen on exercise-induced increase of pulmonary arterial pressure in idiopathic pulmonary fibrosis - Pouwels-Fry, S.; Pouwels, S.; Fournier, et al., C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Introduction: Idiopathic pulmonary fibrosis (IPF) is a severe disease with no known effective therapy. Patients with IPF may develop severe increase of pulmonary arterial pressure (PAP) on exercise, the mechanisms of which is not clearly identified. Objectives: To determine whether oxygen may correct the increase of PAP developed during exercise in patients with IPF. Patients and methods:We performed a prospective study on patients with IPF and no hypoxaemia at rest. The absence of pulmonary hypertension (PH) at rest was confirmed by echocardiography (systolic PAP